Traumatic events and psychopathological symptoms in university students - Bedoya, Erika Yohanna; Ruíz, Sara; Córdoba, Alexander; Rendón, Gabriel David; Ruíz, Gabriel Ignacio; Gómez, Germán David (Revista de Psicopatología y Psicología Clínica, 2020)
Abstract: A non-experimental, cross-sectional and correlational study that aims to analyze the relationship between traumatic events and psychopathological symptoms in 286 university students (76.6% women and 23.4% men) between 18 and 59 years (M = 24.03; SD 7.14) by non-probabilistic convenience sampling. A large part of the sample did not present any traumatic event and those who did showed levels of neutral and/or negative affectation. The most frequent events are the death of a loved one, robbery or assault, divorce of the parents, nervous breakdown, school failure, rejection or failure in a relationship. The least reported events are severe or chronic illness, imprisonment or torture, loss of a child or second marriage. In general, the sample presented low scores in all the psychopathological dimensions. All the variables are related in a statistically significant way, which supports the interaction between traumatic events and various psychopathological symptoms. Keywords: Traumatic events; psychopathological symptoms; anxiety; schizotypy; university students. Eventos traumáticos y síntomas psicopatológicos en estudiantes universitarios Resumen: Estudio no experimental, transversal y correlacional, que busca analizar la relación entre eventos traumáticos y síntomas psicopatológicos en 286 estudiantes universitarios (76.6% mujeres y 23.4% hombres) entre 18 y 59 años (M = 24.03; DE. 7.14) mediante muestreo por conveniencia. Gran parte de la muestra no presentó ningún evento traumático y quienes si los presentaron manifestaron niveles de afectación neutra y/o algo negativa. Los eventos más frecuentes son muerte de un ser querido, robo o asalto, divorcio de los padres, ataque de nervios, fracaso escolar, rechazo o fracaso en una relación. Los eventos menos reportados son enfermedad grave o crónica, encarcelamiento o tortura, pérdida de un hijo o segundo matrimonio. En general la muestra presentó puntuaciones bajas en todas las dimensiones psicopatológicas. Todas las variables se relacionan de manera estadísticamente significativa, con lo cual se soporta la interacción entre eventos traumáticos y diversos síntomas psicopatológicos. Palabras Clave: Eventos traumáticos; síntomas psicopatológicos; ansiedad; esquizotipia; estudiantes universitarios.